2009
DOI: 10.1590/s1415-43662009000200008
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre a produtividade do mamoeiro e o déficit hídrico (ky) na região Norte Fluminense

Abstract: RESUMOTeve-se como objetivo neste trabalho, determinar o coeficiente de resposta ao déficit hídrico na produção de frutos comerciais e totais do mamoeiro, cultivado na região Norte do Estado do Rio de Janeiro. O experimento foi realizado na área de convênio UENF/PESAGRO-RIO, no município de Campos dos Goytacazes, RJ, no período de 25/04/2006 a 18/05/2007, utilizando-se o mamoeiro cultivar Híbrido UENF/CALIMAN01 e um delineamento em blocos casualizados, com cinco tratamentos, correspondendo às reposições de 50%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
1
2
0
4
Order By: Relevance
“…almost 63% more than single spacing plants ( Table 2). The average fruit yield recorded for doublespaced plants is compatible with that referred by Garcia et al (2007), but lower than those reported by Posse et al (2009) and Marinho et al (2010), all of them in studies on papaya (pawpaw). The lower fruit yield values gathered in the present study could be caused by the high air temperatures (25 °C -34 °C range) and low air humidity (37% -73% range) registered during the experimental time, because if air humidity be lower than 60% during papaya flowering phase, most of flowers fall (Paull and Duarte 2011).…”
Section: Resultssupporting
confidence: 90%
“…almost 63% more than single spacing plants ( Table 2). The average fruit yield recorded for doublespaced plants is compatible with that referred by Garcia et al (2007), but lower than those reported by Posse et al (2009) and Marinho et al (2010), all of them in studies on papaya (pawpaw). The lower fruit yield values gathered in the present study could be caused by the high air temperatures (25 °C -34 °C range) and low air humidity (37% -73% range) registered during the experimental time, because if air humidity be lower than 60% during papaya flowering phase, most of flowers fall (Paull and Duarte 2011).…”
Section: Resultssupporting
confidence: 90%
“…Particular atenção deve ser dada ao déficit hídrico uma vez que, além de afetar significativamente a produção das culturas, sobretudo quando ocorre na fase de florescimento e, ainda, pode acarretar em decrementos no aspecto qualitativo, quando ocorre durante o período reprodutivo (Fabeiro et al, 2002;Lovelli et al, 2007;Aujla et al, 2007;Posse et al, 2009;Xiao et al, 2009). Para garantir o sucesso do cultivo nas diferentes fases das culturas, as irrigações devem ser realizadas antes que a disponibilidade de água no solo seja reduzida a níveis que alterem o metabolismo das plantas e, assim, possam comprometer a produção.…”
Section: Introductionunclassified
“…Furthermore, crop water deficit may significantly affect yields and the qualitative aspects of the fruit, particularly when it occurs during the flowering phase or during the reproductive period (AUJLA et al, 2007;LOVELLI et al, 2007;POSSE et al, 2009). …”
Section: Introductionmentioning
confidence: 99%